SEEDING PEACEFUL PREACHING IN THE DIGITAL UNIVERSE: MEDIATIZATION OF PREACHING HUSEIN JA'FAR AL-HADAR ON INSTAGRAM - Qurrota A'yuni; Rulli Nasrullah (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
Social media has an essential role in spreading and transforming Islamic preaching in Indonesia. Through the utilization of various features on Instagram, this article focuses on Husein Ja'far al-Hadar's (HJA) efforts to spread peaceful Islamic preaching in the digital universe for urban millennials. This paper analyzes forms of mediatization in oral, text and visual, both content or captions, that affect HJA's engagement with its followers. This research is qualitative research with a virtual ethnographic approach. Data collection is done through interviews, observation and documentation. This study concludes that HJA's da'wa becomes interesting, light, relaxed and entertaining because it adapts to popular culture and follows social media trends. His simple and concise preaching narrative makes HJA preaching easy to accept and becomes a reference in answering contemporary religious problems. His tolerant preaching contains love, mutual respect, and inclusiveness that answer the unrest of communities wanting to know more about Islam. Changes in his innovative forms of proselytizing and adaptive to Instagram's needs make HJA a role model and figure of a young preacher whose competence is considered.